2000
DOI: 10.1096/fj.00-0014com
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of recombinant human acid sphingomyelinase into Niemann‐Pick disease mice leads to visceral, but not neurological, correction of the pathophysiology

Abstract: An inherited deficiency of acid sphingomyelinase (ASM) activity results in the Type A and B forms of Niemann-Pick disease (NPD). Using the ASM-deficient mouse model (ASMKO) of NPD, we evaluated the efficacy of enzyme replacement therapy (ERT) for the treatment of this disorder. Recombinant human ASM (rhASM) was purified from the media of overexpressing Chinese Hamster ovary cells and i.v. injected into 16 five-month-old ASMKO mice at doses of 0.3, 1, 3, or 10 mg/kg every other day for 14 days (7 injections). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 37 publications
(38 reference statements)
3
92
0
1
Order By: Relevance
“…[9][10][11][12][13] Preclinical studies in an ASM knockout mouse model of NPD demonstrated that biweekly administration of olipudase alfa reduced tissue sphingomyelin concentrations in a dosedependent manner. 14,15 No adverse effects were observed at Novel first-dose adverse drug reactions during a phase I trial of olipudase alfa (recombinant human acid sphingomyelinase) in adults with Niemann-Pick disease type B (acid sphingomyelinase deficiency)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] Preclinical studies in an ASM knockout mouse model of NPD demonstrated that biweekly administration of olipudase alfa reduced tissue sphingomyelin concentrations in a dosedependent manner. 14,15 No adverse effects were observed at Novel first-dose adverse drug reactions during a phase I trial of olipudase alfa (recombinant human acid sphingomyelinase) in adults with Niemann-Pick disease type B (acid sphingomyelinase deficiency)…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Marked elevations in interleukin (IL)-6, granulocyte colony-stimulating factor, and keratinocyte-derived cytokine were detected within hours of dosing, consistent with cytokine storm. 15 This unexpected toxicity occurred after a single dose of olipudase alfa, precluding the involvement of antibody-mediated pathways.…”
mentioning
confidence: 99%
“…Recombinant ASM purified from the culture medium of Chinese hamster ovary (CHO) cells (He et al, 1999) is rapidly taken up from the circulation 1 of ASM knockout mice primarily into liver and spleen, where it is directed to acidified organelles and can degrade SM (Miranda et al, 2000). This finding strongly suggests that enzyme replacement therapy by intravenous infusion of recombinant ASM is a feasible strategy for the treatment of the peripheral symptoms of Niemann-Pick disease as seen in both types A and B.…”
mentioning
confidence: 99%
“…This finding strongly suggests that enzyme replacement therapy by intravenous infusion of recombinant ASM is a feasible strategy for the treatment of the peripheral symptoms of Niemann-Pick disease as seen in both types A and B. However, recombinant ASM does not cross the blood-brain barrier and, therefore, this therapy does not appear to improve ASM levels in the brain or reduce SM (Miranda et al, 2000). It is essential, therefore, that alternatives to enzyme replacement therapies be developed to deal with the profound neurological deficits encountered in NPDA.…”
mentioning
confidence: 99%
“…La plupart sont en effet de type palliatif. Les résultats les plus encourageants sont obtenus par substitution d'enzyme recombinante, glucosidase ou sphingomylinase [41][42][43], et dans une moindre mesure, par diminution du substrat [44][45][46][47]. L'avenir réside dans la mise au point de thérapies géniques visant à réintroduire le gène déficient [48].…”
Section: Sphingolipides Et Maladies Génétiquesunclassified